PEDAGOG-TÁRBIYASHÍNÍŃ KÁSIPLIK KOMPETENTLIGIN RAWAJLANDÍRÍWDA METODIKALÍQ XÍZMETTIŃ ROLI - Saparbayeva, G.A. (SCIENCE and SOCIETY, 2024)
The article talks about the role of methodical activity and self-development in developing the professional competence of teachers of a preschool educational organization, and how it meets the requirements of educators.